(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Positive symptoms become perceptible in patients as schizophrenia progresses. If schizophrenia goes untreated catatonic motor behaviors are develops. Now a day’s catatonia which is a type of disturbed behavior is observed, with less frequency than in past years due to advances in treating schizophrenia. Treatment of schizophrenia by olanzapine and risperidone shows diverse outcomes. Objectives: To assess the response on positive symptoms of schizophrenia by olanzapine and risperidone. Materials and Methods: This study was conducted in Department of Pharmacology and Department of Psychiatry of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period from September 2013 to January 2015. A total of 179 schizophrenia patients fulfilling the inclusion criteria were enrolled and of them 75 patients completed the study, where 40 were in olanzapine treated group and 35 were in risperidone treated group in a 12-weeks assessment where Scale for Assessment of Positive Symptoms (SAPS) was applied. After statistical analysis of scores between intergroup and intra group p<0.05 was considered significant. Results: Treatment with both the olanzapine and risperidone were remarkably effective for progress of positive symptoms of schizophrenia patients but in olanzapine treated group the score was reduced more than that of risperidone treated group and the difference was significant (p<0.05). Conclusion: Olanzapine has responded better on positive symptoms of schizophrenia patients than that of risperidone. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 58-60